Rapid and sensitive microplate assay for screening the effect of silver and gold nanoparticles on bacteria. (August 2009) - Amin, Rehab M; Mohamed, Mona B; Ramadan, Marwa A; Verwanger, Thomas; Krammer, Barbara
Background & aim: Nanomaterials are the leading requirement of the rapidly developing field of nanomedicine and bionanotechnology, and in this respect, nanotoxicology research is gaining great importance. In the field of infections, nanoparticles are being utilized as therapeutic tools against microbes, thus understanding the properties of nanoparticles and their effect on microbes is essential prior to clinical application. The aim of this study was to evaluate a microplate-based assay for monitoring the toxicity of silver and gold nanoparticles on bacteria.Method: Escherichia coli, a Gram-negative bacteria, and Staphylococcus capitis, a Gram-positive bacteria, were exposed to different concentrations of gold and silver nanoparticles.Results: Analysis of bacterial growth showed that the toxicity of silver nanospheres is higher than that of gold nanospheres. The toxicity of silver nanoparticles is dependent on their concentration, whereas in the case of gold nanoparticles, there is no significant toxic effect. Therefore, the described microplate assay could be used as a rapid and sensitive method for detection of bacterial growth inhibition.